Color Stability of Orthodontic Elastomeric Ligatures in the Oral Environment: A Clinical Trial - Marzieh Mazhari; Mehdi Yaghoubi Ashrafi; Sara Gholamian; Mehrnaz Moradinejad (Frontiers in Dentistry)
Objectives: Despite the recent advances in orthodontic appliances, color change of elastomeric ligatures over time remains a problem causing patient dissatisfaction. This study aimed to assess the color stability of different types of orthodontic elastomeric ligatures in the oral environment.